2021
DOI: 10.2174/1573399817666201207200346
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids in the Treatment of Diabetes: Clinical Outcomes and Mechanism to Ameliorate Blood Glucose Levels

Abstract: Background:: For thousands of years, natural food products have been a medicine for diseases that affect the human body, including diabetes mellitus. Lately, several investigations have studied the flavonoids derivatives of plant origins and their biological activity. Given our need to know more mechanisms for treating this disease, Methods:: we will do a thorough research review on treating diabetes mellitus based on flavonoids, its therapeutic potential, and biological action. Results:: Flavonoids reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 163 publications
0
5
0
Order By: Relevance
“…Several potent α-glucosidase inhibitors from plant sources have been identified and have received great attention from the scientific community worldwide as they possess no evident side effects [12,13]. Among them were flavonoids, the most extensively studied compounds as natural antidiabetic agents, associated with a reduction in risk of diabetes in humans, animals and in vitro models [14,15]. Food-derived flavonoids show extremely low toxicity [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Several potent α-glucosidase inhibitors from plant sources have been identified and have received great attention from the scientific community worldwide as they possess no evident side effects [12,13]. Among them were flavonoids, the most extensively studied compounds as natural antidiabetic agents, associated with a reduction in risk of diabetes in humans, animals and in vitro models [14,15]. Food-derived flavonoids show extremely low toxicity [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…While there are observational studies, such as the one by Gao et al (2021), that demonstrate higher dietary intake of flavonoids from fruits is associated with lower risk of GDM development [28], there is a lack of clinical trials examining the effects of flavonoids on GDM management, not risk. Al Duhaidahawi et al (2021) summarized research in type 2 diabetes and concluded that flavonoids help regulate glucose metabolism directly but has yet to be confirmed in patients already diagnosed with GDM [29].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to antimicrobial and anticancer effects, and a preventive effect regarding cardiovascular diseases, flavonoids have helped to combat diabetes and treat autoimmune diseases. [46][47][48][49][50] Anthocyanins belong to the group of flavonoid compounds. Owing to its excellent stability, anthocyanins in Cruciferae show a high bioaccessibility and bioavailability in the human body.…”
Section: Polyphenolsmentioning
confidence: 99%
“…Flavonoids have a long research history in terms of their health benefits. In addition to antimicrobial and anticancer effects, and a preventive effect regarding cardiovascular diseases, flavonoids have helped to combat diabetes and treat autoimmune diseases 46‐50 . Anthocyanins belong to the group of flavonoid compounds.…”
Section: Major Nutrients Of Cruciferous Sprouts and Microgreensmentioning
confidence: 99%